A New Luminescent Zn(II) Coordination Polymer Constructed From Nicotinic Acid and 3, 5-Diamino-1, 2, 4-Triazole Ligands. Issue 1 (2nd January 2016) - Bu, Xianzhong; Chen, Jinquan; Hu, Mingzhen
Abstract : A new Zn(II) coordination polymer, namely [Zn2 (datrz)2 (nic)2 ]n (1 Hdatrz = 3, 5-diamino-1, 2, 4-triazole, Hnic = nicotinic acid), has been obtained through solvothermal reactions of Zn(NO3 )2, Hdatrz and Hnic. The crystal crystallizes in triclinic P -1 space group, a = 9.4379(6) Å, b = 10.0180(6) Å, c = 11.9812(8) Å, α = 73.711(6)°, b = 72.646(6)°, γ = 88.515(5)°, Z = 2. The title compound features a 2D layer structure, which further extends into a 3D supramolecular framework via intermolecular hydrogen bonds. In addition, the luminescent properties of1 were also investigated at room temperature.